Identifying New Factors Associated With Cognitive Decline and Delirium After Transcatheter Aortic Valve Implantation: A Study Protocol - Ghezzi, Erica S.; Psaltis, Peter J.; Loetscher, Tobias; Davis, Daniel; Montarello, Joseph; Lau, Jerrett K.; Delacroix, Sinny; Bourke, Alice; McLoughlin, James; Keage, Megan; Keage, Hannah A. D. (Frontiers in Cardiovascular Medicine, 2021)
Background: Transcatheter aortic valve implantation (TAVI) has become the standard-of-care for treatment of severe symptomatic aortic stenosis and is also being increasingly recommended for low-risk patients. While TAVI boasts positive post-procedural outcomes, it is also associated with cognitive complications, namely delirium and cognitive decline. There is a pressing need for accurate risk tools which can identify TAVI patients at risk of delirium and cognitive decline, as risk scores designed for general cardiovascular surgery fall short. The present effect-finding exploratory study will assess the utility of various measures in the context of ageing and frailty in predicting who will and who will not develop delirium or cognitive impairment following TAVI. The measures we propose include gait, visual symptoms, voice, swallowing, mood and sleep. Methods: This is an observational prospective cohort study focused on identifying pre-procedural risk factors for the development of delirium and cognitive decline following TAVI. Potential risk factors will be measured prior to TAVI. Primary outcomes will be post-procedure cognitive decline and delirium. Secondary outcomes include activities of daily living, quality of life, and mortality. Delirium presence will be measured on each of the first two days following TAVI. All other outcomes will be assessed at 3-, 6- and 12-months post-operatively. A series of logistic regressions will be run to investigate the relationship between potential predictors and outcomes (presence versus absence of either delirium or cognitive decline). Discussion: This study will assess the strengths of associations between a range of measures drawn from frailty and ageing literature in terms of association with cognitive decline and delirium following TAVI. Identified measures can be used in future development of TAVI risk prediction models, which are essential for the accurate identification of cognitive at-risk patients and successful application of pre-procedural interventions. Trial registration: This trial is registered with the Australian New Zealand Clinical Trials Registry (Registration number: ACTRN12618001114235, https://bit.ly/2PAotP5).